Development of a learning management model for science teachers - Saksri Suebsing; Channarong Wisetsat (Institute of Advanced Engineering and Science, 2026)
The goal of this study was to create a learning management model for primary science teachers that considers the factors affecting the learning management strategies of science instructors in the Province of Roi Et. The sample consisted of 300 basic science teachers in the Province of Roi Et and was created via a straightforward random selection of 20 schools. Among the study tools are science learning management manuals, assessments, and surveys. The following statistics were used in the data analysis: mean and standard deviation. The results showed that the science learning management model consists of five steps: i) involvement, ii) survey, iii) justification, iv) detailed description, and v) evaluation. Therefore, it is clear that the elements of learning management and innovation creation are significant factors in this context. The inspiration of having a public mind has a direct impact on the learning management strategies of primary science instructors at the 0.01 level, with an influence value of 0.58.